The Effectiveness of In-Class Debates in Enhancing EFL Learners’ Speaking Skill - Tahar, Asma (My University, 2017)
Being competent in speaking the foreign language, is of focal concern for many learners. In particular, the English language learners, who endeavour to communicate effectively with other users of the target language. However, teaching to communicate in real situations is somehow neglected in EFL context, and students have little exposure to practise the language in the classroom. Therefore, teachers should apply various techniques and activities to enhance their learners' speaking ability and foster their communicative skill. Debating is such an activity through which students filter their English spoken production. The current paper aims to investigate the effectiveness of in-class debates in enhancing learners’ speaking skill. The study is mainly concerned with making use of debates in oral English courses to improve learners’ speaking skill. The research will also put the light on the importance of creating a friendly atmosphere in language class as an attempt to get learners involved to practise the language. To investigate this issue, a questionnaire was administered to second year LMD students at the Department of English (Abdelhamid IBN Badis University of Mostaganem), we relied as well as on classroom observation. We have adopted a descriptive method in order to gather data.
Case study: Second year LMD Students of English at Mostaganem University
Keywords: EFL; Enhancing speaking skill; Communicative skill; Debate